A Systematic Literature Review On Mantra And Meditation - Ji, Om; Mishra, Shubham; Upadhyay, Prem Shankar; Goswami, P.K.; Dash, Swagatika; Sanwal, Kiran (Journal of Neonatal Surgery, 2025)
This systematic literature review examines research on mantra and meditation published between 2001 and 2024, utilizing data traced from the Web of Science. A total of 1,408 studies were initially identified, with 95 studies ultimately included based on relevance and inclusion criteria. The findings highlight significant trends in the field, with notable concentrations in psychology (29 publications), integrative complementary medicine (23), and neurosciences/neurology (13). Other key areas include religion, psychiatry, and general internal medicine. The geographical dispersal of research is dominated by the USA (46 publications), followed by Germany (16) and India (7). The data also reveal an increasing trend in publications, particularly post-2010, peaking in 2021-2023. Articles constitute the largest portion of document types (76), followed by review articles (15), demonstrating the preference for peer-reviewed, original research and comprehensive literature reviews. The findings reflect the growing interest in mantra and meditation across diverse academic disciplines, with aposition on health-related research and interdisciplinary approaches. This increase in publications, particularly in the last decade, highlights a shift toward greater academic productivity and international collaboration